Psychological Origins of Corruption - Zarichanskyi, Oleh (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2022)
Considering the fact, that the vast majority of research on corruption is carried out in the field of law and economics, the purpose of this article is to single out the psychological origins of corruption, which are directly related to the problem of the effectiveness of overcoming it. A deep interrelationship of existential and psychological factors of corruption, which in the context of the spiritual situation of society act as synonyms, has been established. It is noted that in modern studies of corruption, there is a tendency to consider this phenomenon as a "problem of macropsychology", which not only reveals its social, political, and economic aspects, but also sees in it a general spiritual and civilizational problem. It is emphasized that corruption occurs at the intersection of economic, existential and psychological factors. The theoretical approaches of philosophers and psychologists (A. Bandura, E. Fromm, J. Lypovetsky, etc.) to the study of the nature of modern consumer society and the spiritual sense of well-being of a person in such a society are analyzed. Emphasized is the position that excessive consumption acts as a compensator for anxiety. The need for this type of consumption comes from a feeling of inner emptiness, hopelessness, mental confusion, and tension. The direct connection between consumption and spiritual instability of a person is emphasized. The relentless growth of needs while minimizing ethical regulators stimulates the finding of various (unethical and illegal) forms of meeting these needs, which opens a wide path for corruption. It is noted that consideration of the psychological mechanisms of the formation of corrupt behavior contributes to a deeper penetration into the essence of this phenomenon; and the psychological analysis of corruption reveals its important aspect, which is rooted in dependence on consumption. Such a spiritual illness of modern society contributes to the development of corrupt motives and, accordingly, corrupt acts. Three main psychological origins of corrupt behavior are singled out: deprivation; frustration and deviance. Moreover, it is stated that the study of corruption within the framework of deviantology gives the greatest positive effect, because in this case, the negative methods of fighting corruption can be opposed by a positive method.